Trauma In Asika Ikechukwu’s Tamara: A Transitivity Analysis - Ifeoma G, Akabuike; Emmanuel, Asika ikechukwu; Lauretta, Chinyeaka; Anyaeneh, Theodore (Journal of Neonatal Surgery, 2025)
This study analyzed trauma in Asika Ikecukwu’s Tamara by employing Halliday’s transitivity. Trauma is real and many individuals/groups of individuals battle with trauma. Traumatic experiences are devastating and could lead to death. Most often, readers of literary works fail to realize the linguistic structures that reveal themes (main ideas) in a novel. This makes the reader to struggle with meaning/message the author wants to pass across to the audience, hence, this study, A Transitivity analysis of trauma in Asike Ikechukwu’s Tamara with view of finding out the various ways traumatic experiences were represented in the novel through the lexico-grammatical choices of the author, to construe meaning. A total of Sixty (60) clauses were purposely extracted from the novel and the excerpts categorized into participants-processes-circumstances. Textual data were analyzed in line with the objectives of the study, research questions and principles of the theoretical framework adopted. The study reveals that the material process type is the dominant process counted as 22, mental 20, relational 13, verbal 3 and behavioral 2. The write’s use of material process and other process types in the text unveils traumatic experiences of Tamara.